VD_FINDINFO ML / 2023 / 35 vom 27. März 2023 - VD Tribunal cantonal (2023)
RETARD, DÉCISION D'IRRECEVABILITÉ | 56 ch. 2 LP, 138 al. 3 CPC (CH), 145 al. 4 CPC (CH), 239 al. 1 CPC (CH), 239 al. 2 CPC (CH)